Fermentasi Sistem Aerob Dan Anaerob Dalam Pembuatan Cuka Dari Nira Aren (Arenga Pinnata) - Netty Maria Naibaho (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2017)
Vinegar is one of the products that are often utilized by the community to enhance the taste of food. The purpose of this study was to determine the taste of vinegar with the addition of cinnamon and to determine the effect of long fermentation in the production of Neera vinegar. This research was completed by using randomized design with 2 factors, namely the long fermentation and fermentation type (aerobe and anaerobe). The results show that the highest water content was found in anaerobic fermentation with an average of 0.97%. The lower water content was in aerobic fermentation with an average of 0.96%. Since the high pH was at 2 days interval with pH 4, while the low pH was at day 6 that was with pH 3. The results of organoleptic tests for color showed the highest fermentation value on day 6 was with anaerobic fermentation with the average value of 3.70. The highest value of the organoleptic test for aroma was found in day 4 with anaerobic fermentation with an average of 3.60. The organoleptic test showed that anaerobic fermentation had the highest taste rate of 3.6 on average on day 6. Anaerobic fermentation process for 6 days resulted in pH value and organoleptic test preferred by panelists.